2021
DOI: 10.3846/jcem.2021.14900
|View full text |Cite
|
Sign up to set email alerts
|

Causal Mapping to Explore Emergence of Construction Disputes

Abstract: Disputes, frequently encountered in construction projects, can substantially affect project success, necessitating a clear understanding of how and why disputes occur. Previous studies on disputes mostly yielded exhaustive lists or hierarchies of possible causes of disputes, which can hardly be used to understand how these causes come together to form a dispute. To address this gap, this study provides an alternative approach to understand the underlying causes of disputes, and their relationship within a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The five causes located at the highest level can directly and immediately lead to cost overrun. Tanriverdi et al. (2021), for example, developed a causal mapping to examine the causes of construction disputes and concluded that change orders and variations are the most important causes of claims which can both result in high costs and losses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The five causes located at the highest level can directly and immediately lead to cost overrun. Tanriverdi et al. (2021), for example, developed a causal mapping to examine the causes of construction disputes and concluded that change orders and variations are the most important causes of claims which can both result in high costs and losses.…”
Section: Resultsmentioning
confidence: 99%
“…The five causes located at the highest level can directly and immediately lead to cost overrun. Tanriverdi et al (2021), for example, developed a causal mapping to examine the causes of construction disputes and concluded that change orders and variations are the most important causes of claims which can both result in high costs and losses. Kermanshachi et al (2020) concluded that extensive change orders driven by different project stakeholders make project execution more complex and affect project objectives, such as cost, schedule and quality.…”
Section: Discussionmentioning
confidence: 99%
“…, 2019; Saseendran et al. , 2020; Tanriverdi et al. , 2021), outcomes of construction claims (Chaphalkar et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The lack of experience of technical personnel has a substantial impact, including delays in highway or road construction [11] and disputes. Shortcomings such as inadequate skills to handle a claim-related [4] and lack of communication [12], [13] have contributed to a construction dispute. Disputes in construction can be referred to as prolonged disagreements over unresolved claims and protracted conflicts [14], such as delays, payments, and scope changes ( [12], [15].…”
Section: Introductionmentioning
confidence: 99%